Investigation of transmission properties of a tapered optical fibre with gold nanoparticles liquid crystal composite cladding - Moś, Joanna E.; Stasiewicz, Karol A.; Jaroszewicz, Leszek R. (Opto-Electronics Review, 2022)
The article presents a study of a hybrid structure based on the combination of a tapered optical fibre and gold nanoparticles dispersed in a liquid crystal material. Sensitivity to changes of the refractive index of the environment in which the structure is located, as well as the possibility of changing the refractive index of liquid crystals by external factors, such as temperature and electric field, were investigated. Electro- and thermally-induced changes of the refractive index of a liquid crystal through the rotation of a molecule director, which cause changes in the light propagated in a tapered optical fibre, were described. The most important issue in the article is to determine the influence of doping a liquid crystal with gold nanoparticles the concentration of which varies between 0.1 and 0.3 wt.%. The paper presents transmission measurements in a wide optical range depending on voltage, temperature, and frequency changes. Additionally, time courses of the obtained signal were measured. The study shows that the appropriate selection of nanoparticle concentration has a huge impact on the optical wave propagation. The experimental results show that the optical changes obtained for the investigated hybrid structure prefer it for use as an electro-optical switcher, filter, or sensor.